Enfermedades inducidas por drogas: anemia aplásica adquirida, hepatitis medicamentosa y gastritis hemorrágica en el Hospital Nacional Guillermo Almenara Irigoyen agosto 1998 - octubre 2001 - Valencia S., Miguel A. (2004)
The goal of the present research was to establish the relationship cause - effect between drug administration and the presence of acquired aplasic anemia, drug hepatitis and hemorrhagic gastritis, identifying the probable causing drugs. It is applied the deductive analysis by Karch and Lasagna algorithim modilyed by Naranjo et al. The considered criteria for establishing relationship of causality between ethiologic (drug) agent and induced disease were: temporal relationship between suspect drug and induced disease drugs; favorable resolution of the signs, symptoms and lab assay after retirement of probably causing agent; the lab data and clinical analysis that relate in time, the drug and the appearance of the diseases in the study. It was identified 18 cases of acquires aplasic anemia; 15 cases of drug hepatitis and 41 cases of hemorrhagic gastritis. It was concluded that 27,8% of the cases of aplasic anemia and 48,8% of the cases of hemorrhagic gastritis had as a probably ethiologic agent just drugs. The chemiotherapic agents with a 11,1% (5- fluoracil, doxorubicina, metotrexate) in aplasic anemia; and antituberculusic agents with a 20,1% (Isoniazide, Riphampicine , Pirazinamide, Etionamide) in drug hepatitis and the non steroidal antiimflamatory agents with a 29,3% (ibuprophen, Pyroxica) in hemorrhagic gastritis, were the probably main agents that causes the studied diseases from above.